Design, synthesis, and biological evaluation of Bcr-Abl PROTACs to overcome T315I mutation - Liang Jiang; Yuting Wang; Qian Li; Zhengchao Tu; Sihua Zhu; Sanfang Tu; Zhang Zhang; Ke Ding; Xiaoyun Lu (Elsevier, 2021)
Bcr-Abl threonine 315 to isoleucine 315 (T315I) gatekeeper mutation induced drug resistance remains an unmet clinical challenge for the treatment of chronic myeloid leukemia (CML). Chemical degradation of Bcr-AblT315I protein has become a potential strategy to overcome drug resistance. Herein, we first described the design, synthesis, and evaluation of a new class of selective Bcr-AblT315I proteolysis-targeting chimeric (PROTAC) degraders based on GZD824 (reported as Bcr-AblT315I inhibitor by our group). One of the degrader 7o with 6-member carbon chain linkage with pomalidomide exhibits the most potent degradation efficacy with DR of 69.89% and 94.23% at 100 and 300 nmol/L, respectively, and has an IC50 value of 26.8 ± 9.7 nmol/L against Ba/F3T315I cells. Further, 7o also displays substantial tumor regression against Ba/F3-Bcr-AblT315I xenograft model in vivo.